[Ti12In6O18(OOCC6H5)30]: a multifunctional hetero-polyoxotitanate nanocluster with high stability and visible photoactivity. Issue 3 (28th November 2016) - Liu, Shengjun; Hu, Wei; Nath, Jayanta Kr.; Tong, Jing; Hou, Xudong; Liu, Wenlong; Yang, Jinlong; Liu, Bo
Abstract : A stable hetero-polyoxotitanate of [Ti12 In6 O18 (OOCC6 H5 )30 ] produces pronounced photocurrent, and reactive oxygen species (ROS) as well as H2 under visible irradiation. Abstract : We present a novel strategy to improve the stability and optical absorption of polyoxotitanates (POTs) via concurrently fully carboxylate-coordinating and hetero-metal-doping, and illustrate the strategy by an indium doped hetero-polyoxotitanate (h-POT) of a [Ti12 In6 O18 (OOCC6 H5 )30 ] (POTi12 In6 ) nanocluster, which possesses ultrahigh stability in both acid and base aqueous solutions. The nanocluster structurally features a core–shell double wheel structure and a polar cavity. Both experiments and theoretical calculations confirm the semiconductive properties of the nanocluster. Under visible irradiation thePOTi12 In6 nanocluster can produce pronounced photocurrent, and reactive oxygen species for pollutant degradation. Without using any cocatalyst, POTi12 In6 exhibits important visible-light-driven photocatalytic activity for H2 evolution in an aqueous system. This work could render a polyoxotitanate as a new type of visible-photoactive photocatalyst.